Analysis on the Effect of Map Projection System for Area Calculation - Yustisi Lumban-Gaol; Ayu N. Safi’i; Prayudha Hartanto; Tia R. N. Rachma (IPTEK Journal of Proceedings Series, 2019)
Map projection is required for modeling the earth from sphere into flat form. Out of so many types of projection systems, Universal Transverse Mercator (UTM) is the most common map projection system used in Indonesia. The concept of Mercator projection system is to maintain the angle but cause distortion on the area and distance. This will become problem if it is used for calculating an area that require minimum distortion, especially on a large scale. This study aims to find out the effect of the projection system for any scale to the area, and find out the best projections system in Indonesia. In this paper, the area was calculated using 72 projection systems with various scale using MATLAB software. The reference area that considered true was the polygon area of an ellipsoid so the difference between area of ellipsoid and projection can be known. The projection systems that give minimum distortion are the most optimum result. Based on the study, the most suitable projection system for calculating the area with minimal distortion is Collignon for 1: 250,000 scale and 1: 50,000, Eckert II projection system for 1: 25,000 scale and Equal-area Conic Albers Standard projection system for scale 1: 5,000.